2016
DOI: 10.1002/ecy.1567
|View full text |Cite
|
Sign up to set email alerts
|

Seedling performance covaries with dormancy thresholds: maintaining cryptic seed heteromorphism in a fire‐prone system

Abstract: Abstract. The production of morphologically different seeds or fruits by the same individual plant is known as seed heteromorphism. Such variation is expected to be selected for in disturbance-prone environments to allow germination into inherently variable regeneration niches. However, there are few demonstrations that heteromorphic seed characteristics should be favored by selection or how they may be maintained. In fire-prone ecosystems, seed heteromorphism is found in the temperatures needed to break physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Differences in seed dormancy/germination may contribute to seedling recruitment by allowing plants to emerge in a broad range of regeneration niches (Grubb 1977; Coomes and Grubb 2003; Liyanage et al 2016). In B. pilosa , freshly matured central achenes have a relatively low level of dormancy and may germinate across a wide range of temperatures similar to temperature of their natural habitat (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in seed dormancy/germination may contribute to seedling recruitment by allowing plants to emerge in a broad range of regeneration niches (Grubb 1977; Coomes and Grubb 2003; Liyanage et al 2016). In B. pilosa , freshly matured central achenes have a relatively low level of dormancy and may germinate across a wide range of temperatures similar to temperature of their natural habitat (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diaspore heteromorphism, a condition where a genotype produces different morphophysiological types of seeds, has been interpreted as an adaptive trait in heterogeneous environments (Venable 1985; Imbert 2002; Baskin and Baskin 2014). Not only do the diaspores of heteromorphic species look different, but they may differ in numerous other ways, including size/mass (Ellner and Shmida 1984; Venable and Levin 1985; Rocha 1996; Liyanage et al 2016); dispersal ability (Venable 1985; Rocha 1996; Mandák and Pyšek 2001; Zhang et al 2015); dormancy and germination (Corkidi et al 1991; Wang et al 2008; Baskin and Baskin 2014; Zhang et al 2015; Liu et al 2018); and the reproductive allocation of plants grown from heteromorphic seeds (Cheplick and Quinn 1988; Liyanage et al 2016; Zhang et al 2017). These differences range from autecological and population traits to genetic and molecular aspects of biology (Baskin and Baskin 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other variations between seed morphs also occur in seed behaviour without visible morphological differences (Venable, 1985). This type of seed heteromorphism, termed cryptic, has been observed in various species (Leverett and Jolls, 2014; Liyanage et al ., 2016), and is a common, yet rarely documented phenomenon (Venable, 1985; Leverett and Jolls, 2014). The ecological advantages of seed heteromorphism include differences between morphs in competitive ability, dispersion, dormancy, germination time, vulnerability to predators and seedling growth (Matilla et al , 2005; Lu et al ., 2010; Leverett and Jolls, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fire-related dormancy-breaking temperature thresholds vary between PY species (Trabaud and Oustric, 1989; Auld and O'Connell, 1991) and within populations of single species (Liyanage and Ooi, 2015). It has been proposed that such variation has been selected for because of the inherent variability of fire (Trabaud and Oustric, 1989; Ooi et al ., 2014; Liyanage et al ., 2016), which results in variation in soil heating over the area burnt (Bradstock et al ., 1992; Penman and Towerton, 2008). Having different dormancy-breaking temperature thresholds among species can therefore contribute to species co-existence, by distributing germination over space (Trabaud and Oustric, 1989; Ooi et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Having different dormancy-breaking temperature thresholds among species can therefore contribute to species co-existence, by distributing germination over space (Trabaud and Oustric, 1989; Ooi et al ., 2014). It has also been suggested that within-species variation can operate as a bet-hedging mechanism, ensuring that at least some germination is possible across a range of fire severities, and that PY thresholds are maintained by co-varying with seedling characteristics, which ensure that seedling performance matches the post-fire conditions (Liyanage and Ooi, 2015; Liyanage et al ., 2016). Dormancy-breaking threshold temperatures have been used to estimate the potential magnitude of post-fire seedling establishment, depending on the fire severity and/or the amount of soil heating that occurs (Wright et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%